2020
DOI: 10.48550/arxiv.2010.04560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artificial Intelligence based Anomaly Detection of Energy Consumption in Buildings: A Review, Current Trends and New Perspectives

Yassine Himeur,
Khalida Ghanem,
Abdullah Alsalemi
et al.

Abstract: Enormous amounts of data are being produced everyday by submeters and smart sensors installed in different kinds of buildings. If leveraged properly, that data could assist end-users, energy producers and utility companies in detecting anomalous power consumption and understanding the causes of each anomaly. Therefore, anomaly detection could stop a minor problem to become widespread, costly and time-consuming issue. Moreover, this will help in better decision-making to reduce wasted energy and promote sustain… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 216 publications
(259 reference statements)
0
4
0
Order By: Relevance
“…According to the literature, the field of ADD in buildings is progressively leveraging on the application of data analytics techniques [12] for addressing both detection and diagnosis tasks.…”
Section: Related Work and Contribution Of The Papermentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, the field of ADD in buildings is progressively leveraging on the application of data analytics techniques [12] for addressing both detection and diagnosis tasks.…”
Section: Related Work and Contribution Of The Papermentioning
confidence: 99%
“…In this perspective, dimensionality reduction can be used with a low computational cost, for example, for removing irrelevant patterns and redundancy from energy consumption datasets. As reviewed in [12], various techniques were explored to enable the classification of data as normal or anomalous, such as principal component analysis (PCA) [27], linear discriminant analysis (LDA) [28], singular variable decomposition (SVD) [29].…”
Section: Related Work and Contribution Of The Papermentioning
confidence: 99%
“…The QUD is a collection of readings from different mounted devices (e.g. light lamp, air conditioning, refrigerator, and computer) coupled with quantitative details, such as temperature, humidity, ambient light intensity, and space occupation [44]. To the best of the researchers' understanding, QUD is the first dataset in the Middle East in which a normal 240V voltage is used with variable recording duration ranging from 3 seconds to 3 hours [45].…”
Section: Datasets Overviewmentioning
confidence: 99%
“…With regard to anomaly detection, previous studies have employed traditional algorithms, such as the k-nearest neighbors (k-NN), support-vector machine (SVM), decisiontree (DT), as well as deep-learning methods, such as convolutional neural network (CNN), recurrent neural network (RNN), and generative adversarial network (GAN) to obtain energy consumption data [12]. Especially regarding residential load data, Xu et al [13] suggested a detection method that combines RNNs and quantile regression.…”
Section: Introductionmentioning
confidence: 99%